Book review: Tarangini Sriraman. In Pursuit of Proof. (December 2019) - Thachil, Tariq
Tarangini Sriraman. In Pursuit of Proof . New Delhi, India: Oxford University Press, 2018. 323 pages. ₹850. ISBN: 978-0199463510 (Hardback).